2008
DOI: 10.1007/s10517-008-0152-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of potassium and chlorine channels in the regulation of thymocyte volume in rats

Abstract: Regulatory decrease in thymocyte volume under conditions of osmotic stress was abolished by potassium and chlorine channel blockers. Osmotic stress-activated chlorine channels belong to 2 pharmacological types. The maxi-anion channel is sensitive to Gd(3+). The volume-sensitive outwardly rectifying chlorine channel is inhibited with glybenclamide and phloretin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…5B) suggests that a single thymocyte may express several hundreds (∼500 in this particular cell) of VSOR anion channels. Our results would suggest that only a small fraction of them will be active during the GSH release experiment, supposedly because the cells will be restoring their volume by the regulatory volume decrease (RVD) mechanism, which is very prominent in these cells [25], [26]. In addition, swelling-induced membrane depolarization might also diminish the electrochemical driving force for GSH efflux.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5B) suggests that a single thymocyte may express several hundreds (∼500 in this particular cell) of VSOR anion channels. Our results would suggest that only a small fraction of them will be active during the GSH release experiment, supposedly because the cells will be restoring their volume by the regulatory volume decrease (RVD) mechanism, which is very prominent in these cells [25], [26]. In addition, swelling-induced membrane depolarization might also diminish the electrochemical driving force for GSH efflux.…”
Section: Discussionmentioning
confidence: 99%
“…Cell isolation was performed as described previously [24][26]. Briefly, the 6–8 weeks old rats were anaesthetized with halothane or diethyl ether and painlessly euthanized by cervical dislocation; the thymi were dissected and carefully washed with an ice-cold Ringer solution.…”
Section: Methodsmentioning
confidence: 99%
“…Cell isolation was performed as described previously [13,14,38]. Briefly, the 6–8 weeks old mice were anaesthetized with halothane and painlessly euthanized by cervical dislocation; the thymi were dissected and carefully washed with an ice-cold Ringer solution.…”
Section: Methodsmentioning
confidence: 99%
“…Arrazola et al [12] and Soler et al [15] found that osmotic swelling-induced fluxes of K + and Cl − were tightly coupled and were efficiently inhibited by a selective blocker of the K-Cl cotransporter, [(dihydroindenyl)oxy] alkanoic acid (DIOA). However, in our previous pharmacological study, the RVD process in rat thymocytes was completely abolished by blockers of potassium channels and swelling-activated anion channels [14] suggesting involvement of ion channels rather than the coupled K-Cl cotransporter in thymocyte volume regulation under hypotonicity. Here, we provide direct evidence that cell swelling activates two types of the volume-regulated anion channels, the volume-sensitive outwardly rectifying (VSOR) Cl − channel and the maxi-anion channel; and only the VSOR channel is chiefly responsible for the anionic efflux during RVD in thymocytes and is sensitive to DIOA.…”
Section: Introductionmentioning
confidence: 97%
“…For patch-clamping, the cells were cultured in suspension under mild stirring during 3-5 h. All animal experiments were conducted in accordance with the ARRIVE guidelines and approved by the Bioethics Committee of the Institute of Biophysics and Biochemistry. The isolation of thymic lymphocytes (thymocytes) was performed as described previously (Kurbannazarova et al, 2003(Kurbannazarova et al, , 2008(Kurbannazarova et al, , 2011Sabirov et al, 2013). Briefly, the 6-8 weeks old rats, kept in vivarium on an average diet, were anaesthetized with halothane or diethyl ether and painlessly euthanized by cervical dislocation.…”
Section: Cellsmentioning
confidence: 99%